2018
DOI: 10.1039/c8sc00274f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast interligand electron transfer in cis-[Ru(4,4′-dicarboxylate-2,2′-bipyridine)2(NCS)2]4− and implications for electron injection limitations in dye sensitized solar cells

Abstract: Using IR absorption anisotropy, interligand energy transfer in N712 is shown to occur on a sub-ps time scale, and is thus unlikely to limit injection in DSSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…[13][14][15] The sensitizationo fasemiconductor photocatalyst using ad ye, yielding as o-called dye-sensitized photocatalyst (DSP), is au seful strategy to improvet he ability to absorb light in the visible regionb ye xploiting the absorption bands of the surface-immobilized dye. [16][17][18][19][20][21][22][23][24][25] This mechanism is also applicable to Z-schemew ater-splitting photocatalysis composed of oxygen-and hydrogen-evolution photocatalysts coupled with as uitable redoxm ediator. [26][27][28][29] To construct highly active Z-schemew ater-splittingp hotocatalysts, the charge separation efficiency in the DSP mustb ei mproved, and the selective recognition of oxidized or reducedm ediators is importantf or achieving one-way electront ransfer from the oxygen evolutionp hotocatalyst to hydrogen evolution photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] The sensitizationo fasemiconductor photocatalyst using ad ye, yielding as o-called dye-sensitized photocatalyst (DSP), is au seful strategy to improvet he ability to absorb light in the visible regionb ye xploiting the absorption bands of the surface-immobilized dye. [16][17][18][19][20][21][22][23][24][25] This mechanism is also applicable to Z-schemew ater-splitting photocatalysis composed of oxygen-and hydrogen-evolution photocatalysts coupled with as uitable redoxm ediator. [26][27][28][29] To construct highly active Z-schemew ater-splittingp hotocatalysts, the charge separation efficiency in the DSP mustb ei mproved, and the selective recognition of oxidized or reducedm ediators is importantf or achieving one-way electront ransfer from the oxygen evolutionp hotocatalyst to hydrogen evolution photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic water splitting is a simple reaction to produce H 2 as a solar fuel, and, since the discovery of the Honda–Fujishima effect, [6] many studies have been conducted using semiconductor materials [7–12] and perovskite‐type composites [13–15] . The sensitization of a semiconductor photocatalyst using a dye, yielding a so‐called dye‐sensitized photocatalyst (DSP), is a useful strategy to improve the ability to absorb light in the visible region by exploiting the absorption bands of the surface‐immobilized dye [16–25] . This mechanism is also applicable to Z‐scheme water‐splitting photocatalysis composed of oxygen‐ and hydrogen‐evolution photocatalysts coupled with a suitable redox mediator [26–29] .…”
Section: Introductionmentioning
confidence: 99%
“…N3, and its charged variants, belongs to a broader class of transition-metal compounds undergoing rapid and complex charge transfer dynamics, potentially influenced by structural rearrangements, and vastly employed as dyes in dye-sensitized solar cells. , The complex photoinduced dynamics registered for N3 suggests that many states in the excited singlet 1 MLCT manifold might be involved in various CTs and relaxation pathways available to these systems. Previous experimental works already suggested that ILET processes can occur in the Franck–Condon region of the singlet 1 MLCT excited state manifold, i.e., before the intersystem crossing toward the final lowest energy triplet 3 MLCT state, for the extensively studied Ru­(bpy) 3 2+ , , as well as for N3 4– . Recently, we have observed an ultrafast (<25 fs) time for ILET to occur, and additionally, some of the authors have been involved in the modeling of recent two-dimensional electronic-vibrational spectroscopy experiments that proved the crucial importance of vibrational modes affecting either both the Ru-(NCS) charge-donor segment or the dcbpy charge-acceptor portion on the N3 4– molecule, having first evidence of their correlation with many 1 MLCT states and the excited state CT processes .…”
Section: Introductionmentioning
confidence: 88%
“…Previous experimental works already suggested that ILET processes can occur in the Franck−Condon region of the singlet 1 MLCT excited state manifold, i.e., before the intersystem crossing toward the final lowest energy triplet 3 MLCT state, for the extensively studied Ru(bpy) 3 2+ , 60,63−69 as well as for N3 4− . 70 Recently, we have observed an ultrafast (<25 fs) time for ILET to occur, 24 and additionally, some of the authors have been involved in the modeling of recent two-dimensional electronic-vibrational spectroscopy experiments that proved the crucial importance of vibrational modes affecting either both the Ru-(NCS) charge-donor segment or the dcbpy charge-acceptor portion on the N3 4− molecule, having first evidence of their correlation with many 1 MLCT states and the excited state CT processes. 36 Such states, called 1 MLCT A and 1 MLCT B and, respectively, found around 24 400−24 700 cm −1 (410−405 nm) and 25 000−25 300 cm −1 (400−395 nm), were previously shown to be those most vibronically coupled with the final (and energetically lowest) triplet 3 MLCT state (main responsible, along with the initial singlet states, of the electron injection in the semiconductor in the photodevices).…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic makes it ideal for studying the electron transfer process at material interfaces at both the molecular and atomic levels. For instance, mid-IR spectroscopy has been used to study the carrier dynamics in metal complexes, organic-dye-sensitized solar cells, and semiconductors, thereby providing valuable dynamical information regarding the ultrafast injection and relaxation of the excited states of these materials. In other words, with its ability to probe the vibrational states of the reactants and products simultaneously, mid-IR spectroscopy is a useful tool that can provide an enhanced understanding of the intricate dynamics of charge transfer in various material systems.…”
Section: Introductionmentioning
confidence: 99%